Prognostic Impact of Soluble P-Selectin on Long-Term Adverse Cardiovascular Outcomes in Patients Undergoing Percutaneous Coronary Intervention - Tscharre, Maximilian; Vogel, Birgit; Tentzeris, Ioannis; Freynhofer, Matthias K.; Rohla, Miklos; Wojta, Johann; Weiss, Thomas W.; Ay, Cihan; Huber, Kurt; Farhan, Serdar (Thrombosis and Haemostasis, 2019)
Background Soluble P-selectin (sP-selectin), a biomarker of inflammatory pathologies including cardiovascular disease, is known to have pro-atherosclerotic effects such as the ability to increase leukocyte recruitment and modulate thrombotic response. We aimed to assess the impact of sP-selectin on long-term major adverse cardiovascular events (MACE) in patients after coronary stenting for coronary artery disease.Methods We analysed 733 patients of a single-centre registry undergoing percutaneous coronary intervention (PCI) between 2003 and 2006. Plasma samples were analysed for sP-selectin antigen concentration with an enzyme-linked immunoassay. The study population was categorized according to sP-selectin quartiles. Endpoint of the study was long-term MACE, a composite of all-cause death, myocardial infarction (MI) and stroke.Results Of the total patient cohort, 361 (49.2%) patients were admitted for stable coronary artery disease and 372 (50.8%) for acute coronary syndrome. Median age was 64 years and 70.7% were male. After a mean follow-up period of 9.7 years, MACE occurred in 344 (46.9%) patients. The primary endpoint components of all-cause death occurred in 211 (28.8%), MI in 88 (12.0%) and ischaemic stroke in 45 (6.1%) patients. After adjustment for confounders, patients in the 2nd, 3rd and 4th quartile were at higher risk for MACE compared with the 1st quartile (hazard ration [HR], 1.234 [0.899–1.695], p = 0.193; HR, 1.480 [1.085–2.019], p = 0.013; and HR, 1.571 [1.115–2.152], p = 0.004). sP-selectin as continuous variable model was significantly associated with MACE after adjustment (HR per 1 ng/mL increase of 1.009 [95% confidence interval, 1.002–1.017]; p = 0.016).Conclusion Elevated levels of sP-selectin were associated with increased risk for long-term MACE in patients undergoing PCI.
Keywords: soluble P-selectin; percutaneous coronary intervention; long-term major adverse cardiovascular outcome